Malperfusion syndrome in acute type A aortic dissection: Thinking beyond the proximal repair. Issue 11 (21st August 2022) - Bayamin, Karama; Power, Adam; Chu, Michael W. A.; Dubois, Luc; Valdis, Matthew
Abstract: Background and Objective: Malperfusion syndrome (MPS) is associated with the highest mortality and major morbidity risk in patients with acute Type A aortic dissection (TAAD). The timing of the open proximal aortic repair in the presence of MPS remains debatable given variability in clinical presentation and different local treatment algorithms. This paper provides an up to date and comprehensive overview of published outcomes and available techniques for addressing malperfusion in the setting of acute TAAD. Methods: We have reviewed published data from the major aortic dissection registries including the International Registry of Acute Aortic Dissection, the German Registry for Acute Aortic Dissection In Type A, and the Nordic Consortium for Acute Type A Aortic Dissection, as well as the most up to date literature involving malperfusion in the setting of acute TAAD. This data highlights unique strategies that have been adopted at aortic centers internationally to address malperfusion in this setting pre‐, intra‐, and postoperatively, which are summarized here and may be of great clinical benefit to other centers treating this disease with more traditional methods. Results: The review of the available data has definitively shown an increased mortality up to 43% and morbidity in patients presenting with MPS in the setting of acute TAAD. More specifically, preoperative MPS has been shown to be an independent predictor of mortality with mesenteric malperfusion associated with the worst mortality outcomes from 70% to 100%. Addressing MPS pre or intraoperatively is associated with significantly reduced mortality outcomes down to 4%–13%. Conclusion: Adapting a dynamic and easily accessible diagnostic method for the comprehensive assessment of different forms of malperfusion (dynamic/static) and incorporating it within the surgical plan is the first step toward early diagnosis and prevention of malperfusion related complications.